Acidentes graves em trabalhadores que atuam na construção Civil, no município de Uberlândia-MG (2013 a 2015) - Magalhães, Silvia Fonseca (2017)
This study aims to analyze the profile of injured workers both formal and informal working in construction, in the Municipality of Uberlândia (MG), in the period 2013 to 2015. This is an exploratory research, an approach quali-quantitative analysis focused on the investigation of workplace accidents considered serious. For both, research was carried out in literature books and scientific articles relevant to the topic, as well as a survey and analysis of penalty payments for accidents received on the SINAN and the CEREST (Reference Center in Occupational Health). The results indicate that the typical accidents have higher incidence among workers with lower educational level, being the occupation of a mason responsible for the largest number of records. This study also points to the urgent need for expansion projects for clarification and continuing education in the process of job security in Uberlândia (MG).